Aroma properties of homologous series of 2,3-epoxyalkanals and tr-4,5-epoxyalk-2-enals. - Büttner, Andrea; Schieberle, Peter (Journal of Agricultural and Food Chemistry, 2001)
A few odor-active epoxyaldehydes, formed during lipid peroxidation, have recently been reported as intense aroma compounds in foods. However, very little is known about their flavor properties in general. Syntheses of homologous trans-2,3-epoxyalkanals (C(6)-C(12)) and trans-4,5-epoxy-(E)-2-alkenals (C(7)-C(12)) followed by structural characterization using mass spectrometry (MS/EI; MS/CI) and (1)H NMR measurements were performed. An evaluation of their odor qualities and odor thresholds by gas chromatography-olfactometry revealed the following: within the trans-2,3-epoxyalkanals, the odor quality changed from grassy for the compounds with six and seven carbon atoms to citrus-like or soapy for aldehydes with eight and more carbon atoms. The odor thresholds lay in the range of 3-15 ng/L (in air) and were nearly identical within the series; however, a slight minimum was measured for trans-2,3-epoxyoctanal to trans-2,3-epoxydecanal. In the series of the trans-4,5-epoxyalk-(E)-2-enals the C(10) compound was characterized by the lowest odor threshold of 0.6-2.5 pg/L of air. However, all trans-4,5-epoxy-alk-(E)-2-enals smelled intensely metallic.<br